The Effect of FOXA3 Overexpression on Hepatocyte Differentiation and Liver Regeneration in a Fah cKO Mouse ModelSummary - Shao Li; Chupeng Ou; Jiajun Zhang; Min Zeng; Kangyan Liang; Qing Peng; Yi Gao (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Stimulated by injury or disease, hepatocytes can regenerate and repair liver tissues through proliferation and differentiation. Partial hepatectomy and liver transplantation are effective treatments for liver diseases. This study investigated the effect of FOXA3 on cell differentiation in HepaRG cell lines under 2- and 3-dimensional culture conditions. Methods: Experiments were performed using a HepaRG cell line that stably overexpressed FOXA3 (RF3) and hepatocyte-specific functions. Moreover, a Fah conditional knockout mouse model (Fah cKO mice) was constructed using the CRISPR-Cas9 method and treated with RF3 spheroids for transplantation. Various molecular biology and immunostaining experiments were performed to assess liver function, hepatocyte structure, and expression levels of cell cycle–related proteins. Results: HepaRG cells that overexpressed FOXA3 had hepatocyte-specific functions. RF3 spheroids expressed liver markers following gene and protein expression analysis. After RF3 spheroid transplantation, Fah cKO mice exhibited increased survival, reduced weight loss, normalization of liver function and hepatocyte structure, and enhanced expression of hepatocyte differentiation factors. However, the expression of cell cycle–related proteins, including p53 and p21, was decreased in vivo. Injection of an HNF4α antagonist revealed that inhibition of HNF4α effectively suppressed the regenerative capacity of the liver after RF3 spheroid transplantation, resulting in an increase in the number of p53- and p21-positive cells and a decrease in the expression levels of liver function–related genes. Conclusions: FOXA3 plays an important role in hepatocyte function. RF3 spheroid transplantation had a therapeutic effect in the Fah cKO mouse model, improving liver function and promoting liver regeneration.